2020
DOI: 10.1111/jfbc.13227
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of selenium‐resistant bacteria and advancement under enrichment conditions for selected probiotic Bacillus subtilis (BSN313)

Abstract: The main aim of this work was to screen, isolate, and identify a probiotic selenium (Se)‐resistant strain of Bacillus subtilis, using the 16S rDNA sequencing approach and subsequently optimize conditions. Initially, conditions were enhanced in two univariate optimization environments: shakings flask and a bioreactor. After solving optimization for selected variables, conditions were further optimized using orthogonal array testing. The results were further evaluated by the analysis of variance, in support of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…This probiotic strain has the higher capability to show resistance in selenium enriched medium. BSN313 strain would safely be used as a probiotic tool for the production of SeNPs for nutritional and medicinal purpose [94]. So the present study was designed for developing probiotic nano-selenium containing products/selenium nano-sized particles (SeNPs) via a biosynthetic approach using probiotic Bacillus Subtilis BSN313 in an economic and easy way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This probiotic strain has the higher capability to show resistance in selenium enriched medium. BSN313 strain would safely be used as a probiotic tool for the production of SeNPs for nutritional and medicinal purpose [94]. So the present study was designed for developing probiotic nano-selenium containing products/selenium nano-sized particles (SeNPs) via a biosynthetic approach using probiotic Bacillus Subtilis BSN313 in an economic and easy way.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus Subtilis BSN313previously isolated from traditional Chinese "Jiuqu" [94] was used in this study.Strain (frozen at −80 • C) was thawed on ice and streaked on LB medium plates, by means of an inoculation loop and incubated at 37 • C for 12 h. A single colony was inoculated into a pre-sterilized 10 mL tube containing 4 mL of LB broth and grown at 37 • C for 12 h at 220 rpm shaking speed.…”
Section: Senps Synthesizing Capability 441 Strain Activation and Preparation Of Inoculummentioning
confidence: 99%
“…As reported by Miletić et al [45], the medicinal fungus Coriolus versicolor grown in medium supplemented with 10 and 20 mg Se/L could accumulate 970 and 1300 µg/g of Se, respectively. Ullah et al [46] showed that the probiotic bacteria Bacillus subtilis BSN313 grown in Se-enriched medium at the dose of 12 µg/mL could bind 2.123 µg Se/g. Egressy-Molnár et al [47] studied the process of Se binding by Hericium erinaceus (lion's mane mushroom).…”
Section: Se Bioaccumulationmentioning
confidence: 99%
“…Se is usually referred to as a nutritional antioxidant, but this effect is mainly attributed to selenium-containing proteins and not to pure Se [ 162 ]. SeNPs have been shown to have better antioxidant activity than other chemical forms of Se and also reduce the possibility of its toxicity [ 40 ].…”
Section: Senps As Anticancer Agents Beyond the Toxicitymentioning
confidence: 99%
“…Selenium-resistant bacteria convert Se intracellularly to a non-toxic organic form until their Se tolerance limit is exceeded, and they begin to produce the nano-sized Se particles (Se 0 ) (intracellularly or extracellularly). For example, in our recent studies, a probiotic Bacillus subtilis (BSN313) accumulated Se in its cell, up to 12 µg/mL, and beyond this level, it began to produce SeNPs [ 40 , 41 ]. It is known that SeNPs are only synthesized by those bacteria that have the ability to resist selenium metal.…”
Section: Introductionmentioning
confidence: 99%